RELASI SOSIAL BUDAYA ATA KROWE DAN GUNUNG MAPITARA - Putri Novita Taniardi (BRIN, 2017)
This paper discusses about a relation between Mount Mapitara and Ata Krowe. Mount Mapitara is a sacred mountain that has a special meaning for Ata Krowe. Ata Krowe is a name for Krowe people who lived in Krowe adat area in Kabupaten Sikka, East Nusa Tenggara on Flores Island. The question raised in this paper is: what is the meaning of Mount Mapitara for Ata Krowe and how does that meaning was symbolized by material culture among Ata Krowe. To answer these questions, the research has been conducted to explore the way material culture were being used as symbols that related to the existence of Mount Mapitara. This study is applying this study was applying theory of symbols which refer to Michael Shanks and Christopher Tilley’s theory of ideology, symbolic power, and ritual communication. This theory was applied to identifiy the use of material cultures as symbol in a certain place and to define the symbol that related to Mount Mapitara. The research result indicate that there is material culture named wu’a mahe that has special meaning for Ata Krowe. Wu’a mahe is a stone altar that believed as a place where the ancestor had lived, before they were getting purified and move into Mount Mapitara as a perpetual place to stay. This paper is focusing on the relation between Mount Mapitara and Ata Krowe that can be seen from the use of material culture as symbols.